DIPLOMASI DIGITAL DAN IMPLEMENTASI APLIKASI SAFE TRAVEL DI KEMENTERIAN LUAR NEGERI - Andela Anggleni (Jurnal Caraka Prabu, 2021)
Public Service-Based Information Technology and Communication (ICT), Electronics Neighborhood/Pillars of Citizens (e-RT/RW) (Study of e-Government in Kelurahan Talang Semut Kecamatan Bukit Kecil Kota Palembang). This study is based on the new way to manage public sector-oriented management services to the community forward, rather than the interests of the government. E-Government Program is a program of e-RT/RW Surabaya. The results showed the program e-RT/RW sourced from Palembang Mayor Factors supporting the program e-RT/RW in the Kelurahan Talang Semut, Bukit Kecil, Palembang is the full support of the government and relevant parties, the basic service standards and infrastructure are qualified. Whereas the inhibiting factor is the public interest, a lack of internal party support, and lack of maintenance of infrastructure. From the research, the researchers suggest that the necessary socialization harder, but not merely socialization but also training to people to operate online. Transparent financial accountability. Holding intense communication forum, addition of website content, and control of technical problems with a thorough evaluation.